PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS XI PEMASARAN 1 SMK NEGERI 1 SURAKARTA TAHUN AJARAN 2015/2016 - Sandy Kristiara; Sunarto Sunarto; Sudarno Sudarno (Department of Economics Education, Universitas Sebelas Maret, 2017)
This research aims to improve the learning activities of students in class XI Marketing 1 Selling Services subject, at State Vocationa1 High School1 Surakarta, through the application of a problem-based learning model.The study was based on classroom action research and was carried out through two cycles. There are steps in each cycle was planning, acting, observing, and reflecting. Participants comprised the 30 students in class XI Marketing 1 at State Vocationa1 High School 1 Surakarta, in academic year 2015/2016. The data sources were teachers of Selling Services subject, students, and documentation. Technique collection of the data were used including observations, interviews, documentation, and tests. The data analysis technique used comparative-descriptive analysis and critical analysis.Based on the analysis result, a significant improvement of learning activities was occurred from pre-cycle learning to the first cycle to second cycle. It can be seen from the percentage before applying the problem-based learning model, students learning activities for visual activities was 58.75%, oral activities was 42.92%, listening activities was 60.42% and mental activities was 54.17%. In cycle I, students learning activities for visual activities was 75.83%, oral activities was 63.75%, listening activities was 77.08%, and mental activities was 70%. In cycle II, students learning activities for visual activities was 80%, oral activities was 75.83%, listening activities was 83.92% and mental activities was 77.50%. It can be concluded that the application of a problem-based learning model can improve the learning activities of students in class XI Marketing 1 at State Vocationa1 High School 1 Surakarta on Selling Services subject.